Effects of Sub Lethal Concentration of Cypermethrin on the Biochemical, Behavioural and Haematological Parameters of Rohu (Labeo rohita) Fingerlings - Sadawni P Varangia; M. K Yadav; Shriparna Saxena; Deepak Kher (Archives of Current Research International, 2025)
This study aims to examine and assess the harmful effects of the pyrethroid insecticide cypermethrin on rohu (L. rohita) fingerling. The acute median lethal concentration (LC50) was determined by exposing fish to four different concentrations (2 ppb, 5 ppb, 10 ppb, and 15 ppb) over a 96-hour period and the LC50 value was identified as 4.996 ppb. Based on the concentration obtained fish were exposed to the sub lethal concentration (0.025, 0.05 and 0.1 ppb) and one control with no chemical for a duration of 30 days for further studies to assess the impact of chronic toxicity. A sub-lethal toxicity evaluation indicates significant changes in blood parameters, characterized by an increase in total leucocytes count and glucose levels, alongside a decrease in total erythrocytes count, packed cell volume (PCV), haemoglobin (Hb), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), and mean corpuscular haemoglobin concentration (MCHC). There was also a decrease in biochemical parameters such as albumin, globulin, and total protein. Abnormal behavioural changes observed include loss of equilibrium, increased opercular movement, restlessness transitioning to lethargy, gill mucus secretion, repeated mouth movements, and twitching or convulsions. This study revealed that even minimal exposure to cypermethrin can negatively affect fish, causing notable alterations in behavioural, biochemical and haematological parameters.